Selection Criteria of Energy Storage System Supplier : Action research in a case company - Kurkinen, Nea (My University, 2024)
Due to the growth of renewable energy, the interest in energy storage has been rising all around the world. The need for this research came from the case company which engages in energy storage business. Specifically, the case company was preparing the supplier base to meet increasing customer demands by extending their global portfolio in the US during 2022. The time COVID-19 was affecting normal business practices and the company was forced to adapt the new ways of working. During the same time changing global market dynamics were affecting the ES supplier selection criteria. This action research focus filling the research gaps regarding the supplier selection process steps and supplier selection criteria for ES use. There are a lot of relevant materials available for supplier selection and sourcing on a general level, but no academic material can be found in the specific market area of interest. To fulfil the study objectives, both theoretical and em-pirical approaches were adopted for this study. The primary data source was qualitative data where the data was collected from internal workshops, group discussion, questionnaire re-sponses, semi-structured group discussions and academic literatures. The secondary data source was quantitative data and the data records consist of uploaded data from the Salesforce platform. The platform was the used tool during the eRFQ process. The case was conducted with an action research method. The research showcased the Kraljic matrix use when analysing the portfolio recommendations for the case company. In addition, the suita-ble supplier evaluation criteria for ES use were developed with the inspiration of Carter’s 10 C approach. The developed ES-specific supplier evaluation method was the PS + 10 C ques-tionnaire. Answers to the PS + 10 C questionnaire were analysed by adapting the AHP charac-teristics to the decision matrix. The research is part of the case company’s risk management scope and could be utilized in case a supplier selection needs to be made without full access to the factory. The action re-search results indicate that strategic supplier selection can be conducted without full access to the factory. The outcomes of the study were detailed supplier selection process steps and supplier evaluation criteria for ES use. In addition to these, the decision matrix was used to bring more visibility for internal stakeholders regarding the selection reasoning. Overall, the supplier selection process steps could be utilized to other industries as well. For supplier evaluation criteria, the recommendation is to modify according to sourced product charac-teristics. As one of the research outcomes was that the identified driving factor with supplier evaluation criteria was the sourced product characteristics. By developing the sourced prod-uct-specific questionnaire, organization can understand suppliers’ capabilities and justify the pre-selection. The decision matrix approach supports supply management to address com-plex issues and accordingly, the decision matrix use is not limited to being utilized in other industry areas.

Uusiutuvan energian kasvun myötä kiinnostus energian varastointiin on kasvanut ympäri maailmaa. Tutkimustarve tälle tutkimukselle tuli energian varastointijärjestelmän toimittajalta, joka valmisteli toimittajakantaa vastaamaan asiakkaiden kasvaviin vaatimuksiin. Yritys oli laajentamssa toimittajaportfoliotaan Yhdysvaltoihin vuoden 2022 aikana. Tuolloin COVID-19 vaikutti totuttuihin liiketoimintakäytäntöihin ja yritys joutui sopeutumaan uusiin toimintatapoihin. Samaan aikaan muuttuva energiamarkkina vaikutti yrityksen toimittajan valintakriteereihin. Tutkimuksessa keskitytään täyttämään tutkimusaukot liiittyen toimittajavalintaprosessiin sekä kehittämään toimittajan valintakriteerejä. Toimittajavalintaan ja hankintaan on saatavilla kattavasti relevanttia tutkimusmateriaalia, mutta akateemista materiaalia ei löydy energiavarastoinnin osalta. Tutkimuksen tavoitteiden saavuttamiseksi tutkimus toteutettiin toimintatutkimuksena ja tutkimukselle omaksuttiin sekä teoreettisia että empiristisiä lähestymistapoja. Ensisijainen tietolähde oli laadullinen tieto, jossa tiedot kerättiin sisäisistä työpajoista, puolistrukturoiduista ryhmäkeskusteluista, toimittajien kyselyvastauksista, ja akateemisesta tutkimuskirjallisuudesta. Toissijainen tietolähde oli määrällinen ja materiaali koostuu Salesforce-alustan ladatuista aineistosta, jota käytettiin työkaluna eRFQ-prosessin aikana. Tutkimuksessa hyödynnettiin Kraljic-matriisia, jota käytettiin tapausyhtiön portfolion analysointiin. Sopivat toimittaja-arviointikriteerit energiavarastoinnin toimintakenttään kehitettiin Carterin 10 C -lähestymistavan innoittamana. Toimittaja-arviointikriteeristönä käytettiin PS + 10 C -kyselyä. PS + 10 C -kyselyyn annetut vastaukset analysoitiin mukauttamalla AHP:n ominaisuudet päätösmatriisiin. Tutkimus on osa yrityksen riskienhallintaa ja toteutettua lähestymistapaa voidaan hyödyntää, mikäli toimittajavalinta joudutaan tekemään ilman täyttä pääsyä tehtaalle. Tutkimustulokset osoittavat, että strateginen toimittajavalinta voidaan tehdä ilman täyttä pääsyä tehtaalle. Tutkimuksen tuotoksia olivat yksityiskohtainen toimittajavalintaprosessi ja energia varastoinnin toimittaja-arviointikriteerit. Päätösmatriisia hyödynnettiin, jotta sisäisille sidosryhmille saatiin tarvittavaa lisänäkyvyyttä valintaperusteissa. Toimittajan valintaprosessivaiheita olisi mahdollista hyödyntää myös muilla toimialoilla. Toimittajan arviointikriteereitä suositellaan muokkaamaan hankittavan tuotteen ominaisuuksien mukaan, sillä yksi tutkimustuloksista oli, että liikkeellepanevana tekijänä toimittajan arviointikriteereissä oli hankittavan tuoteen ominaisuudet. Kehittämällä tuotteen ominaisuuksien mukaisen kyselyn, organisaatio voi ymmärtää toimittajien kyvykkyyttä ja perustella esivalintaa. Päätösmatriisilähestymistapa tukee tarjonnan hallintaa monimutkaisten kysymysten käsittelemiseksi ja voidaan hyödyntää muillakin toimialoilla.
Keywords: fi=Tuotantotalous (kauppatieteet)|en=Industrial Management|; Master's Programme in Industrial Management